Treatment outcomes of initial differential antiretroviral regimens among HIV patients in Southwest China: comparison from an observational cohort study. Issue 3 (30th March 2019) - Kang, Ruihua; Luo, Liuhong; Chen, Huanhuan; Zhu, Qiuying; Liao, Lingjie; Xing, Hui; Zhu, Jinhui; Shen, Zhiyong; Lan, Guanghua; Tang, Zhenzhu; Shao, Yiming; Yang, Wenmin; et al.
Abstract : Objectives: China has continued to expand antiretroviral therapy (ART) services and optimise ART guidelines in an effort to significantly reduce and prevent mortality and transmission rates among HIV patients. However, no study to date has compared treatment outcomes of initial differential antiretroviral regimens among HIV patients in a real-world setting in China. This study aimed to compare the effects of different ART regimens on treatment outcomes among adults. Design: Observational retrospective cohort study. Setting: Data from 2011 to 2013 in Guangxi, China. Participants: Patients aged ≥18 years (n=25 732) were selected. Results: A total of 25 732 patients were included in this study. The average mortality and attrition rate were 2.64 and 4.98, respectively, per 100 person-years. Using Cox proportional hazard models, zidovudine-based (AZT-based) regimen versus stavudine-based (D4T-based) regimen had an adjusted HR (AHR) for death of 0.65 (95% CI 0.58 to 0.73); the AHR of tenofovir-based (TDF-based) versus D4T-based regimens was 0.81 (95% CI 0.71 to 0.92), and of lopinavir–ritonavir-based (LPV/r-based) versus D4T-based regimens, 1.19 (95% CI 1.04 to 1.37). AZT-based versus D4T-based regimens had an AHR for dropout of 0.89 (95% CI 0.81 to 0.97); this ratio for TDF-based versus D4T-based regimens was 0.88 (95% CI 0.80 to 0.98), and for LPV/r-based versus D4T-based regimens, 1.42 (95% CI 1.27 to 1.58). AZT-based and TDF-based regimens had a lower risk compared with D4T-based regimens, while LPV/r-based regimens had a higher risk. High gastrointestinal reactions and poor adherence were observed among HIV patients whose initial ART regimen was LPV/r-based. Conclusions: Our study found that the treatment outcomes of initial ART regimens that were AZT-based or TDF-based were significantly better than D4T-based or LPV/r-based regimens. This finding could be related to the higher rates of gastrointestinal reactions and poorer adherence associated with the LPV/r-based regimens compared with other initial ART regimens.